2017
DOI: 10.1021/acs.jpcc.6b11972
|View full text |Cite
|
Sign up to set email alerts
|

Factors Favoring Ferroelectricity in Hafnia: A First-Principles Computational Study

Abstract: The surprising ferroelectricity displayed by hafnia thin films has been attributed to a metastable polar orthorhombic (Pca2 1 ) phase. Nevertheless, the conditions under which this (or another competing) ferroelectric phase may be stabilized remain unresolved. It has been hypothesized that a variety of factors, including strain, grain size, electric field, impurities and dopants, may contribute to the observed ferroelectricity. Here, we use first-principles computations to examine the influence of mechanical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
168
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(178 citation statements)
references
References 37 publications
(58 reference statements)
9
168
0
1
Order By: Relevance
“…Materlik et al calculated the free energy of various phases with varying strain, and the free energy of the t-phase or the o-phase decreases with decreasing tensile strain compared to that of the m-phase. [26] These previous studies strongly suggest that a decrease in the m-phase fraction is expected when the tensile stress in doped HfO 2 thin films is released during the heating phase of in situ XRD. [26] These previous studies strongly suggest that a decrease in the m-phase fraction is expected when the tensile stress in doped HfO 2 thin films is released during the heating phase of in situ XRD.…”
Section: Wwwadvelectronicmatdementioning
confidence: 85%
See 2 more Smart Citations
“…Materlik et al calculated the free energy of various phases with varying strain, and the free energy of the t-phase or the o-phase decreases with decreasing tensile strain compared to that of the m-phase. [26] These previous studies strongly suggest that a decrease in the m-phase fraction is expected when the tensile stress in doped HfO 2 thin films is released during the heating phase of in situ XRD. [26] These previous studies strongly suggest that a decrease in the m-phase fraction is expected when the tensile stress in doped HfO 2 thin films is released during the heating phase of in situ XRD.…”
Section: Wwwadvelectronicmatdementioning
confidence: 85%
“…[63] Instead, the Pmn2 1 polar o-phase was energetically more favorable compared to the experimentally observed Pca2 1 o-phase. [23] Thus, Batra et al [26] suggested that various factors including compressive strain and electric field need to be combined to stabilize the Pca2 1 o-phase. [23] Thus, Batra et al [26] suggested that various factors including compressive strain and electric field need to be combined to stabilize the Pca2 1 o-phase.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
See 1 more Smart Citation
“…This discovery is of great interest to the semiconductor industry and has led to intensive experimental [3][4][5][6][7][8][9][10][11][12][13][14] and theoretical [9,[15][16][17][18][19][20][21][22] research, because these materials are believed to avoid the problems typical for the traditional ferroelectric materials (such as lead zirconate titanate) during integration into microelectronic devices. However, precise identification of the phase(s) in these films is problematic due to experimental limitations such as the broadness of the thin-film diffraction spectra, unknown film texture and strain fields, and possible presence of multiple phases within a single film.…”
mentioning
confidence: 99%
“…The free energy change that may lead to formation of a metastable structure can be due to a combination of finite-temperature (primarily vibrational entropy) effects, finite-size (surface) effects, strain, and "doping" (alloying). These aspects have recently been discussed from a theoretical perspective [19][20][21][22]45]; in particular, changes in the relative free energy of several HfO 2 , ZrO 2 , and HfZrO 4 phases have been estimated by Materlik et al [19], who reported that within a wide range of experimentally reasonable conditions and for film thicknesses in 9nm…30 nm range the vibrational entropy, surface, and strain contributions are well within <∼180 meV/f.u. The changes due to intentional "doping" (alloying) need be evaluated on a case-by-case basis but can be expected to be <<∼ 50 meV/f.u.…”
mentioning
confidence: 99%